Pelatihan Kewirausahaan: Mencari Gagasan Usaha Baru dengan Pendekatan SCAMPER Untuk Pelajar SMA - Terra Saptina Maulani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
In facing the ever-evolving challenges of the times, creative and innovative thinking has become one of the essential competencies that must be possessed by the younger generation, particularly high school students. Creativity is not only useful in academic contexts but is also highly relevant to the development of entrepreneurial spirit. The earlier students are introduced to the process of generating business ideas, the greater their opportunities to develop their potential and create employment in the future. However, not all students have adequate access to or understanding of how to generate original and applicable business ideas. Therefore, a systematic and easy-to-apply approach is needed to assist them in the process of discovering new business ideas. One creative method that can be utilized is the SCAMPER approach (Substitute, Combine, Adapt, Modify, Put to Another Use, Eliminate, and Rearrange). This approach is a creative thinking technique aimed at modifying or developing existing products, services, or ideas into something new and valuable. Through this community service activity, the implementation team seeks to provide training and mentoring for high school students in exploring potential business ideas using the SCAMPER approach. It is expected that students will understand the creative thinking process in the context of entrepreneurship and be able to generate business ideas that are aligned with their surrounding environment and market needs.